9d+11=11d-9

Simple and best practice solution for 9d+11=11d-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9d+11=11d-9 equation:



9d+11=11d-9
We move all terms to the left:
9d+11-(11d-9)=0
We get rid of parentheses
9d-11d+9+11=0
We add all the numbers together, and all the variables
-2d+20=0
We move all terms containing d to the left, all other terms to the right
-2d=-20
d=-20/-2
d=+10

See similar equations:

| X+19+x+13=5x+14 | | 4x-13=2x37 | | -15+x/3=-27 | | 9.013+55.1=s | | 130-(3x+5)=180 | | 12/15=18/x | | -3(5+5n)=5n+5 | | 0.25x+2=-5/8x-5 | | 6z+10=3z+55 | | 2t2=72 | | 3=1/4x-3 | | 2n^2+10-28=0 | | 4x-7.2=x+2.3 | | -3.6e-7.2=12.7-6.1e.1 | | –7u+9=–10u | | 5+1.5x=23 | | n-36.1=23.1 | | 2x​+(​14)+​(x​38)=180 | | 3x+4(x-8)-x=3/4(10x+15) | | 2x-1-2x-1=10x-12 | | 0.3c+1.5=0.4-0.8 | | 0=1x-7 | | R=0.8220−y | | 33/4(2a−6)+12=25(3a+20) | | 3x–(2x+4)=19 | | 6n+3(5n+6)=4(1+5n) | | -27=-3+4w | | x-3-x/5=3 | | 2y=6(-6)+56 | | 7.9x–2–3.2x–10=2.8+x | | 3(y+–48)=-81 | | 13.21-10.1=r |

Equations solver categories